Surface-controlled dissolution rates: a case study of nanoceria in carboxylic acid solutions. Issue 5 (4th April 2019) - Grulke, Eric A.; Beck, Matthew J.; Yokel, Robert A.; Unrine, Jason M.; Graham, Uschi M.; Hancock, Matthew L.
Abstract : Nanoparticle dissolution in local milieu can affect its ecotoxicity and therapeutic applications. Abstract : Nanoparticle dissolution in local milieu can affect their ecotoxicity and therapeutic applications. For example, carboxylic acid release from plant roots can solubilize nanoceria in the rhizosphere, affecting cerium uptake in plants. Nanoparticle dispersions were dialyzed against ten carboxylic acid solutions for up to 30 weeks; the membrane passed cerium-ligand complexes but not nanoceria. Dispersion and solution samples were analyzed for cerium by inductively coupled plasma mass spectrometry (ICP-MS). Particle size and shape distributions were measured by transmission electron microscopy (TEM). Nanoceria dissolved in all carboxylic acid solutions, leading to cascades of progressively smaller nanoparticles and producing soluble products. The dissolution rate was proportional to nanoparticle surface area. Values of the apparent dissolution rate coefficients varied with the ligand. Both nanoceria size and shape distributions were altered by the dissolution process. Density functional theory (DFT) estimates for some possible Ce(iv ) products showed that their dissolution was thermodynamically favored. However, dissolution rate coefficients did not generally correlate with energy of formation values. The surface-controlled dissolution model provides a quantitative measure for nanoparticle dissolution rates: further studies of dissolution cascades should lead to improved understanding of mechanisms and processes at nanoparticle surfaces.